Variabilidade espacial de atributos dendrométricas do eucalipto e de um neossolo quartzarênico a partir da aplicação de calcário ou lama de cal + oxyfertil - Lima, Elizeu de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The fertilization using cellulosic waste used in eucalyptus forestry systems is a great soil conservation practice, since it provides fertilizer saving is descompactante restores good chemical, physical and biological conditions and, above all, increases the productivity of the timber, and prevents waste is deposited in inappropriate places. The objective of this study was to evaluate the spatial variability of individual productivity of Eucalyptus urograndis trees according to the attributes of a Entisol Typic soil in order to highlight specific management zones in order to use the residue of cellulose extraction as sustainably fertilizers to the environment. In 2014, in the experimental area of the Bom Retiro Farm's owned by Eldorado Celulose Brazil in the city of Três Lagoas, located in the Brazilian Cerrado conditions were installed three experimental mesh containing 50 sampling grids totaling 1 ha each experimental grid. Linear and spatial correlations were examined between the plant and the soil in order to highlight specific management areas in order to return the cellulose waste as fertilizer to sustainably environment. While the studied plant attributes were height (Hei), diameter at chest hight (DCH), and wood volume (VOL). Soil attributes were mechanical resistance to penetration (RP), gravimetric moisture (GM), sand, silt, clay, phosphorus (P), organic matter (OM), hydrogen potential (pH), potassium (K + ), calcium (Ca 2+ ), magnesium (mg 2+ ), aluminum (Al 3+ ), sum of bases (SB) and cation exchange capacity (CEC), collected from 0 to 0.20 and 0.20 to 0.40 m depth. Statistical analysis was comprised of: initial descriptive analysis of the attributes, analysis of linear correlation, spatial and temporal between them and the geostatistic analysis, in order, highlight conditions that provide increased productivity of place forests through fertilization held the cellulosic waste. The phosphorus, organic matter and ...

A adubação por meio de resíduos celulósicos utilizada em sistemas silviculturais de eucalipto é uma excelente prática conservacionista do solo, uma vez que proporciona economia de fertilizantes, é descompactante, restabelece boas condições químicas, físicas e biológicas e, sobretudo, aumenta a produtividade da madeira, além de evitar que esses resíduos sejam depositados em locais inadequados. O objetivo deste estudo foi avaliar a variabilidade espacial da produtividade individual das árvores de Eucalyptus urograndis em função dos atributos de um Neossolo Quartzarênico com vistas a evidenciar zonas específicas de manejo no intuito de utilizar o resíduo da extração de celulose na forma de fertilizantes de maneira sustentável ao ambiente. No ano de 2014, na área experimental da Fazenda Bom Retiro de propriedade da Eldorado Brasil Celulose localizada no município de Três Lagoas, situada nas condições do Cerrado Brasileiro foram instaladas 3 malhas experimentais contendo 50 pontos amostrais totalizando 1 ha cada malha experimental. Foram analisadas as correlações lineares e espaciais, entre planta e solo com vistas a evidenciar zonas específicas de manejo no intuito de retornar os resíduos de celulose na forma de fertilizantes de maneira sustentável ao ambiente. Os atributos avaliados da planta foram a altura (ALT) e o diâmetro à altura do peito (DAP). Os atributos do solo foram resistência do solo à penetração (RP), umidade gravimétrica (UG), teores de Areia, Silte, Argila, fósforo (P), matéria orgânica (MO), valores de potencial hidrogeniônico (pH), teores de potássio (K + ), cálcio (Ca 2+ ), magnésio (Mg 2+ ), alumínio (Al 3+ ), valores de soma de bases (SB) e capacidade de troca catiônica (CTC), coletados nas profundidades de 0,00-0,20 e 0,20-0,40 m. A análise estatística foi compreendida da análise descritiva inicial dos atributos, análise das correlações lineares, espaciais e temporais entre...
Keywords: Solos florestais; Geologia - Métodos estatísticos; Solos - Manejo; Solos - Conservação; Forest soils